Revisiting the Online Shopper’s Behaviour in Indonesia: The Role of Trust and Perceived Benefit - Widyastuti, Widyastuti; Hartini, Sri; Artanti, Yessy (International Journal of Industrial Engineering and Management, 2020)
This study attempts to analyze the factors that influence attitudes toward online shopping in Indonesia. The population in this study is consumers who have experience buying products online through social media or e-commerce. The implication of the study is enriching the behavioural marketing studies about factors that influence online product purchases and suggest the marketers create a more effective marketing strategy based on different customer level of trust. The study results showed that perceived benefit and trust are the driving factors of consumer attitudes to make online purchases. In this study, perceived benefit functions as a mediator of trust influence on attitude. This study reveals that high levels of trust influence consumer attitudes toward online shopping while at low levels of trust, consumer attitudes will be more influenced by perceived benefits. Article history: Received (August 20, 2020); Revised (November 18, 2020); Accepted (November 18, 2020); Published online (December 3, 2020)